2006
DOI: 10.1902/jop.2006.060128
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Celecoxib and Dexamethasone for the Prevention and Control of Postoperative Pain After Periodontal Surgery

Abstract: The findings of this study suggest that the preemptive and postoperative use of celecoxib or dexamethasone were effective in the management of postoperative pain following open-flap debridement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
119
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(121 citation statements)
references
References 23 publications
2
119
0
Order By: Relevance
“…Traditionally, impacted third molar extractions and periodontal surgery have served as excellent models for testing analgesic and anti-inflammatory drugs (19,20,22). The dental literature presents few studies evaluating oral administration of glucocorticoids for the prevention and control of postendodontic pain (1,14,(24)(25)(26) and no evaluations with oral prednisolone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, impacted third molar extractions and periodontal surgery have served as excellent models for testing analgesic and anti-inflammatory drugs (19,20,22). The dental literature presents few studies evaluating oral administration of glucocorticoids for the prevention and control of postendodontic pain (1,14,(24)(25)(26) and no evaluations with oral prednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to use a preoperative, single oral dose of prednisolone for the control and prevention of postendodontic pain. Oral administration was preferred because this technique is clinically effective and convenient; the use of intramuscular or intravenous injection might lead to discomfort and fear and is not well-accepted by some patients (1,14,19,24). Most patients and dentists would prefer to provide an anti-inflammatory agent immediately before or selfadministered as needed by the patient after anesthesia has worn off.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, preemptive antiinflammatory drugs may prevent hyperalgesia, reducing postoperative pain and discomfort and the consumption of analgesics. In mucoperiosteal flap surgery for scaling and root planing (17) and in crown lengthening (18), no significant differences for the intensity of pain were demonstrated when both anti-inflammatories (SAID and NSAID) were compared as preemptive and postoperative medications. Steffens et al (25) also showed no significant difference for pain between the SAID (8 mg dexamethasone) and NSAID (120 mg etoricoxib) Groups; this was also true for mucoperiosteal flap surgery for scaling and root planing, but the medications were administered only in the preemptive period.…”
Section: Discussionmentioning
confidence: 99%
“…For all of these evaluated aspects, no differences were observed between the SAID and NSAID groups, confirming the homogeneity of experimental groups and supporting the outcomes obtained in the study. These assessments were not carried out in other studies (16,17,(25)(26)(27)30), which could affect the interpretation of individual morbidity data.…”
Section: Discussionmentioning
confidence: 99%